Proceedings of the International Conference on Economics, Law and Education Research (ELER 2021) 2021
DOI: 10.2991/aebmr.k.210320.016
|View full text |Cite
|
Sign up to set email alerts
|

Activities of Illegal Weapons Criminal Component of Hybrid Threats

Abstract: The paper focuses on the study of hybrid threats in the civil security sector in Ukraine. It is substantiated, based on the factor analysis, the hypothesis of existence of hybrid threats related to the spread of certain types of crime in Ukraine, in particular the activities of illegal armed groups. An empirical study based on the expert survey's results in the system of bodies of the Ministry of Internal Affairs of Ukraine on identification and assessment of hybrid threats in the civil security sector, as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…The methodological basis of the research are general scientific methods: analysis [12] and synthesis, comparison, grouping [13], abstraction and others. The theoretical basis are the studies on innovative activity, profit and cost management from the viewpoint of financial management.…”
Section: The Methodological Basismentioning
confidence: 99%
“…The methodological basis of the research are general scientific methods: analysis [12] and synthesis, comparison, grouping [13], abstraction and others. The theoretical basis are the studies on innovative activity, profit and cost management from the viewpoint of financial management.…”
Section: The Methodological Basismentioning
confidence: 99%
“…Analysis of existing approaches to assess various conditions and aspects of EFS of defense enterprises has been performed, in particular: identification of typical problems in defense enterprises [4,5] in the context of modern economic security [6], a systematic approach to strategy for the economic security of Ukraine's defense industry in the context of European integration [7], and in the context of forced remilitarization of its economy [8], economic and financial technologies at the enterprises [9][10][11] confirmed that there is an urgent need to improve and implement integrated rating approaches to such evaluation, taking into account the shortcomings of existing approaches and increase their adaptability to modern market trends by increasing efficiency of such assessment (rapid assessment) [12,13] and determining the list of EFS indicators. Given that, a rapid assessment of the current state of EFS of defense enterprises is proposed to be carried out according to the following method.…”
Section: Methodsmentioning
confidence: 99%
“…Criminal law regulation in the field of fiscal relations is the subject of research of a large constellation of scientists and practitioners who make hypotheses, substantiate models and forecasts, identify shortcomings of legal norms and their application. This process involves conducting on the appropriate methodological basis of security research of an applied nature, using empirical data not only statistical content (which is not excluded) but also modern risk-oriented approaches, with the development and scientific substantiation of research hypotheses, focusing on their threats and risks distribution [1].…”
Section: Research Analysismentioning
confidence: 99%